Reconfigurable Intelligent Surfaces Between the Reality and Imagination - Asst. Prof. Haider ALRikabi; Adheed Sallomi; Hasan Khazaal; Ahmed Magdy; Iryna Svyd; IVAN OBOD (Wasit Journal of Computer and Mathematics Science)
One interesting idea that could improve wireless communication systems is reconfigurable intelligent surfaces or RIS. To control the spread of wireless signals, RIS uses a plethora of tiny, inexpensive, and customizable reflecting devices. Signal strength, energy consumption, spectrum efficiency, and adaptability to changes in the wireless environment can all be improved by altering the phase shift of the reflecting elements. This is how RIS works. 5G and beyond, the IoT, and smart cities are just a few of the many potential uses for RIS. More study is required before this technology can reach its full potential since it is still in its infancy. Still, RIS is going to be big in the next generation of wireless networks. A great deal of excitement has enveloped the whole 6G development industry. There has been no shortage of grandiose and frequently unfounded assertions that, in reality, the creation of a full-duplex 5G technology that can introduce new services is just around the corner, even though self-interference cancellation schemes for full-duplex communications and the difficulties of building full-duplex base stations have long been known.